Oscillator model approximation applied to 2D materials: Energy loss of relativistic charged particles - Segui, Silvina; Gervasoni, Juana Luisa; Arista, Nestor Ricardo; Mišković, Zoran L. (Elsevier Science, 2021)
Fil: Segui, Silvina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina